2012
DOI: 10.1074/jbc.m111.322800
|View full text |Cite
|
Sign up to set email alerts
|

Leptin-induced Epithelial-Mesenchymal Transition in Breast Cancer Cells Requires β-Catenin Activation via Akt/GSK3- and MTA1/Wnt1 Protein-dependent Pathways

Abstract: Background: Leptin promotes breast tumor progression and is overexpressed in breast tumors. Results: Leptin induces EMT in breast cancer cells via concurrent modulation of Akt/GSK3␤ and MTA1/Wnt1 axes to mediate ␤-catenin activation. Conclusion: ␤-Catenin is required for leptin-induced EMT in breast cancer cells. Significance: Learning how leptin regulates EMT is important for understanding leptin-mediated breast cancer growth and metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
153
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(165 citation statements)
references
References 63 publications
8
153
1
3
Order By: Relevance
“…Cellular signaling pathways, including the Wnt/β-catenin, ERK/MAPK, and PI3K/ Akt pathways, have been found to be aberrantly activated and play vital roles in the development and progression of breast cancer (35)(36)(37). Among these pathways, the prometastatic functions of Wnt/β-catenin signaling in breast cancer have been well documented (35,38). Notably, unlike in other cancer types, the mutations in β-catenin are rare, but the expression and/or nuclear localization of β-catenin is often abnormal in breast cancer, indicating a constitutive activation of Wnt/β-catenin signaling (9,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular signaling pathways, including the Wnt/β-catenin, ERK/MAPK, and PI3K/ Akt pathways, have been found to be aberrantly activated and play vital roles in the development and progression of breast cancer (35)(36)(37). Among these pathways, the prometastatic functions of Wnt/β-catenin signaling in breast cancer have been well documented (35,38). Notably, unlike in other cancer types, the mutations in β-catenin are rare, but the expression and/or nuclear localization of β-catenin is often abnormal in breast cancer, indicating a constitutive activation of Wnt/β-catenin signaling (9,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…However, when this pathway is activated, GSK3β phosphorylates β-catenin, triggering its ubiquitination and subsequent proteasomemediated degradation. Therefore, GSK3β regulates EMT and metastasis via its phosphorylation by AKT [111]. Melatonin, by inhibition of AKT, leads to inhibition of EMT and the development of a metastatic phenotype [112].…”
Section: Antimetastatic Effectsmentioning
confidence: 99%
“…In addition to activating cell proliferation, leptin also poses a risk to breast cancer patients through its ability to influence epithelial to mesenchymal transition (EMT). Yan et al (2012) demonstrated that leptin increases beta-catenin levels which are essential for promoter recruitment which leads to leptin-induced EMT and tumor formation. Beta-catenin levels are increased through leptin-induced phosphorylation of glycogen synthase kinase 3 beta (GSK3 beta) by both activated Akt and by activation of Wnt signaling through MTA1 (Yan et al, 2012).…”
Section: Obesitymentioning
confidence: 99%